Steep increases in biomass demand: the possibilities of short rotation coppice (SRC) agro-forestry - Raslavičius, Laurencas; Azzopardi, Brian; Kopeyka, Aleksandr K.; Šaparauskas, Jonas (Technological and Economic Development of Economy, 2015)
At current usage levels, short rotation coppice (SRC) biomass could be considered as an untapped resource. There is a worldwide interest to extend its sustainable production significantly in a decade to come. However, the cultivation of energy crops is very site-specific and the exploitation of SRC biomass is a relatively new trend in biomass application for heat and power production with little information on its cultivation patterns and appropriate combustion technologies. In fact, documented biomass conversion technologies’ impacts in the energy sector and their commercialisation are limited. This paper aims to present a summary of technical characteristics for different biomass conversion technologies. These characteristics are not necessarily unique to all types and possible modifications of the biomass conversion technologies applied for many countries. However, the lack of technical knowledge have created situations that were previously impossible to be solved without the aid of numerous research and development activities. The developers did not capture all of the economic benefits that the technology provides which would help to reach its technical accomplishment and commercial execution.